An Experimental Study on Hydrogen Storage Capabilities Improvement of the TiFe-H-2 - Halıcıoğlu, Recep; Bayrak, Mustafa; İşcan, Bahattin; Akbalık, Fırat (TAYLOR & FRANCIS INC, 2012)
This study aimed to increase the percentage of the storage capacity of TiFe alloys, which are used for hydrogen storage. The TiFe alloys are capable of very high pressure storage. In this study, for the purpose of activation of storage alloy in low pressures, the required parameters were applied one by one. After about 3–4 hours of grinding, it was observed that the storage capacity was increased by about five times. In the study for determining the iteration number, it was clarified that, by applying about 10 times charge-discharge process, the storage rate was increased by about 15 times. It was concluded by the experimental research that, with a maximum of 10% of the carbon addition, TiFe alloy purity was degraded and storage rate increased at a rate of 27%.
Keywords: Hydrogen; Hydrogen storage; Metal-hydride; TiFe